Evaluation of genetic diversity of some Zucchini yellow mosaic virus-infected cucurbits based on sodium dodecyl sulfate-polyacrylamide gel electrophoresis, inter simple sequence repeat and start codon targeted molecular tools - Shrouk E.E. Farg; Shafik D. Ibrahim; Samir Mahgoub; Atef S. Sadik; Mamdouh H. Abdel-Ghaffar (Novel Research in Microbiology Journal)
The aim of this study was to evaluate the genetic diversity of some Zucchini yellow mosaic virus (ZYMV)-infected cucurbits compared to the healthy plants based on three molecular tools. When sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDSPAGE) analysis was used to determine the genetic variability of four cucurbits infected with ZYMV compared to the healthy ones, a total of 15 storable protein bands were recorded. The experimental results showed that DNA polymorphisms included 38 polymorphic DNA fragments that were generated using the five inter simple sequence repeat (ISSR-PCR) used primers. The maximum identity (%) among the ZYMV-infected and healthy samples was 59, 56, 45, 40, 30, and 29 % for the plant samples of watermelon, squash, cantaloupe, qethaa, cucumber, and luffa samples, respectively. Phylogenetic tree of DNA polymorphisms confirmed the genetic relationship between each of the healthy samples of watermelon and cucumber, healthy samples of qethaa and cucumber, ZYMV-infected samples of watermelon and squash, and ZYMV-infected samples of kantaloupe and qethaa. Numbers of nine start codon targeted (SCoT) primers were used to determine the DNA fingerprinting of six ZYMinfected cucurbit species compared to the healthy plants of the same species. A total of 88 polymorphic DNA fragments were distributed as follows: 13, 7, 10, 6, 9, 10, 15, 8, and 10, which were generated using SCoT-02, SCoT-03, SCoT-04, SCoT-06, SCoT-08, SCoT-11, SCoT-12, SCoT-13, and SCoT-14 primers, respectively. The DNA polymorphisms of the six ZYMV-infected cucurbit species showed identities that ranged from 32 to 79 % using nine SCoT primers compared to the healthy species.